Bloodstream infections after solid-organ transplantation. Issue 3 (2nd April 2016) - Kritikos, Antonios; Manuel, Oriol
Abstract: Solid-organ transplantation (SOT) has become the preferred strategy to treat a number of end-stage organ disease, because a continuous improvement in survival and quality of life. While preventive strategies has decreased the risk for classical opportunistic infections (such as viral, fungal and parasite infections), bacterial infections, and particularly bloodstream infections (BSIs) remain the most common and life-threatening complications in SOT recipients. The source of BSI after transplant depends on the type of transplantation, being urinary tract infection, pneumonia, and intraabdominal infections the most common infections occurring after kidney, lung and liver transplantation, respectively. The risk for candidemia is higher in abdominal-organ than in thoracic-organ transplantation. Currently, the increasing prevalence of multi-drug resistant (MDR) Gram-negative pathogens, such as extended-spectrum betalactamase-producing Enterobacteriaciae and carbapenem-resistant Klebsiella pneumoniae, is causing particular concerns in SOT recipients, a population which presents several risk factors for developing infections due to MDR organisms. The application of strict preventive policies to reduce the incidence of post transplant BSIs and to control the spread of MDR organisms, including the implementation of specific stewardship programs to avoid the overuse of antibiotics and antifungal drugs, are essential steps to reduce the impact of post transplant infections on allograft and patient outcomes.